2008
DOI: 10.1523/jneurosci.3419-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Enhances Cranial Visceral Afferent Synaptic Transmission to the Solitary Tract Nucleus

Abstract: Cranial visceral afferents travel via the solitary tract (ST) to contact neurons within the ST nucleus (NTS)and activate homeostatic reflexes. Hypothalamic projections from the paraventricular nucleus (PVN) release oxytocin (OT) to modulate visceral afferent communication with NTS neurons. However, the cellular mechanisms through which OT acts are poorly understood. Here, we electrophysiologically identified second-order NTS neurons in horizontal brainstem slices by their low-jitter, ST-evoked glutamatergic EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 45 publications
9
143
1
1
Order By: Relevance
“…These synchronous EPSCs conform to parabolic variance-mean amplitude relationships indicating that ST axons have a high probability of release (ϳ90% in 2 mM external Ca 2ϩ ) and activate an average of 18 active zone release sites (Bailey et al, 2006b;Andresen and Peters, 2008;Peters et al, 2008). Interestingly, even multiple convergent ST inputs perform independently (Peters et al, 2011;McDougall and Andresen, 2013), which implies that ST synaptic release zones are quite selfcontained with clear spatial delimitations.…”
Section: Cav-sourced Calcium Drives Synchronous Vesicle Releasementioning
confidence: 75%
See 1 more Smart Citation
“…These synchronous EPSCs conform to parabolic variance-mean amplitude relationships indicating that ST axons have a high probability of release (ϳ90% in 2 mM external Ca 2ϩ ) and activate an average of 18 active zone release sites (Bailey et al, 2006b;Andresen and Peters, 2008;Peters et al, 2008). Interestingly, even multiple convergent ST inputs perform independently (Peters et al, 2011;McDougall and Andresen, 2013), which implies that ST synaptic release zones are quite selfcontained with clear spatial delimitations.…”
Section: Cav-sourced Calcium Drives Synchronous Vesicle Releasementioning
confidence: 75%
“…؊ afferents ST afferents lacking TRPV1 have myelinated axons (Jin et al, 2004), are relatively rare, and have indistinguishable synchronous release compared with TRPV1 ϩ afferents (Andresen and Peters, 2008). Neurons receiving these afferents serve as a natural "control" for comparison to the C-fiber TRPV1 ϩ afferent phenotype.…”
Section: Cavs Only Contribute To Synchronous Release On Trpv1mentioning
confidence: 99%
“…Thus, central vagal afferent endings not only are conduits of signals arriving from the gut, but also may be directly engaged by signals converging onto the NTS from other brain areas. Several anorexic and orexigenic signals have been shown previously to modulate neurotransmission from central vagal afferent endings, including oxytocin (Peters et al, 2008), ghrelin (Cui et al, 2011), and serotonin (Cui et al, 2012). Whether these and other signals also influence food intake by engaging the gut-to-brain circuit via direct activation of central vagal afferent endings merits future investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Oxytocinergic terminals are evenly distributed throughout the NTS (23,35), and OT-immunoreactive axons are closely apposed, suggesting synaptic contacts, with second-order NTS neurons (35). Peters et al (35) showed that OT released from OTergic axons acts on a subset of second-order NTS neurons to enhance afferent visceral transmission via presynaptic (i.e., increased probability for glutamate release) and postsynaptic (increased inward current by closure of K ϩ channels) mechanisms. Therefore, activation of PVN-NTS OTergic projections causes a slowing of HR via at least two different mechanisms: modulation of afferent signaling and a direct effect of depolarizing and exciting NTS neurons.…”
Section: Discussionmentioning
confidence: 99%